Dynamics of genetic and somatic trade-offs in ageing and mortality - Danny Arends; David G. Ashbrook; Suheeta Roy; Lu Lu; Zachary Sloan; Arthur G. Centeno; Kurt H. Lamour; João Pedro de Magalhães; Pjotr Prins; Karl W. Broman; Saunak Sen; Sarah J. Mitchell; et al. (Nature, 2026)
Abstract DNA variants modulate mortality risks across an entire lifespan but their dynamic age-dependent effects have not been resolved in any species for either sex. Here we mapped variants that shape mortality using an actuarial approach, starting with a base population of 6,438 pubescent mice and ending with 559 survivors that lived beyond 1,100 days of age. Twenty-nine Vita loci influence lifespan with strong age- and sex-specific effects. Most act during distinct stages with polarities that often invert with age, but a minority have consistent age-dependent effects in one or both sexes. A separate set of 30 Soma loci influence correlations between body mass and life expectancy. Nineteen Soma loci mediate higher mortality in larger young mice, whereas 11 mediate lower mortality in larger old mice. All effects are stronger in male mice than in female mice. Vita and Soma loci form epistatic networks split strictly by sex. These findings provide a genetic bridge between evolutionary theories of ageing and molecular mechanisms that can guide interventions to extend healthy lifespan.